Medijske reprezentacije in prakse diskriminacije priseljencev v intersekcijski perspektivi - Mandelc, Damjan (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2024)
T he article addresses the phenomenon of mass migration through an intersectional analysis, highlighting the interaction of discriminatory practices and exploring common exclusion mechanisms in the case of two minority groups: Muslim women and migrants/refugees. The starting point of the analysis is the media discourse on two legal documents addressing the ban of Muslim women’s headgear and the problem of illegal migration (the Marrakesh Declaration). The results of the research are applied to a broader reflection on the causes and consequences of discriminatory policies on minority and immigrant communities.
Keywords: discrimination; diskriminacija; immigrants; intersectionality; intersekcija; media representation; medijske reprezentacije; migracije; migrations; priseljenci